The Planetary Turn Relationality and Geoaesthetics in the Twenty-First Century - Elias, Amy; Moraru, Christian (Northwestern University Press, 2015)
A groundbreaking collection that pursues the rise of geoculture as an essential framework for arts criticism, The Planetary Turn shows how the planet-as territory, sociopolitical arena, space of interaction for life, and artistic theme-is increasingly the conceptual and political dimension in which artists picture themselves and their work. In an introduction that comprehensively defines the planetary model of art, culture, and cultural-aesthetic interpretation, the editors explain how the planet is emerging as distinct from older concepts of globalization, cosmopolitanism, and environmentalism and is becoming a new ground for work in literature, art, and social humanities. Written by internationally recognized scholars, the twelve essays illustrate the unfolding of a new vision of potential planetary community that retools earlier models based on the nation-state or political "blocs" and reimagines cultural, political, aesthetic, and ethical relationships for the post-Cold War era.